Comparative Analysis of Akebia trifoliata Fruit Softening at Different Flesh Ripening Stages Using Tandem Mass Tag Technology - Niu, Juan; Sun, Zhimin; Shi, Yaliang; Huang, Kunyong; Zhong, Yicheng; Chen, Jing; Chen, Jianhua; Luan, Mingbao (Frontiers in Nutrition, 2021)
Owing to its medicinal and high nutritional values, Akebia trifoliata can be considered as a new type of medicinal and edible homologous resources, and it has begun to be widely cultivated in many areas of China. Over-softening of fruit would affect the sensorial quality, utilization rate, and consumer acceptance of the fruit postharvest. However, fruit softening has not been characterized and the molecular mechanism underlying A. trifoliata fruit softening during ripening remains unclear. A comparative proteomic analysis was performed on the fruit at three developmental stages using tandem mass tag technology. In total, 2,839 proteins and 302 differentially abundant proteins (DAPs) were identified. Bioinformatics analysis indicated that most DAPs were implicated in oxidoreductase activity, protein domain-specific binding and pyruvate metabolism. Moreover, 29 DAPs associated with cell wall metabolism, plant hormone, and stress and defense response pathways were validated using quantitative PCR. Notably, pectinesterase, pectate lyase, and β-galactosidase, which are involved in cell wall degradation, as well as gibberellin regulated protein, cysteine protease, thaumatin-like protein and heat shock proteins which is involved in plant hormone, and stress and defense response, were significantly up-regulated in softening fruit compared with the levels in non-softening fruit. This indicated that they might play key roles in A. trifoliata fruit softening. Our findings will provide new insights into potential genes influencing fruit softening traits of A. trifoliata, which will help to develop strategies to improve fruit quality and reduce softening-related losses.